A interferência da tributação indutora como estímulo do consumo de etanol como combustível de baixa emissão de carbono - Câmara, Renan Aversari (2016)
The constitutional responsibility of the State to ensure the environmental protection ultimately result in environmental policies aimed at sustainable development. This proposal results from the fact that the environment is a public good, subject to valuation, and their non-inclusion in economics results in increased degradation. The hypothesis of the study focuses on the fact that the absence of the constitutional principle of protection of the environment in the national tax system and exclusion of inducing taxation in the national development policy and national environmental policy ultimately induce consumer goods and damaging services to environmental preservation and protection of natural resources. And it aims to show that inducing taxation instrument works as an environmental protection tool and sustainable development, working on direct interference of costs and prices on certain economic activity through the increase or decrease in taxes, according to state interests. Specifically intended to spell out the formation of fuel prices, in particular ethanol, with an emphasis on tax (Tax on the Circulation of Goods and on Transport Services Rendered Interstate and Intermunicipal and Communication - ICMS, mainly) being used as an environmental preservation mechanism. The results of the analysis show that, using this tool, it is possible that the state can induce a practical "green" in the fuel sector, leading him to a sustainable development and also to environmental protection.